Implant-supported prosthesis under progressive loading protocol stimulates alveolar bone growth in patients with severe alveolar bone atrophy. Retrospective case series - Anitua, Eduardo; Piñas, Laura; Alkhraisat, Mohammad H. (Frontiers in Dental Medicine, 2024)
The jaw with severe bone atrophy is a difficult challenge when rehabilitating with dental implants. To be able to place dental implants in the most severe cases and to achieve an increase in bone volume by means of the tension transmitted by the load is a novelty. This work provides data on the alveolar bone changes in a severely atrophic mandible that has been treated with implant supported prosthesis under progressive loading protocol.This study reported on 3 patients with completely edentulous mandible. In all cases, implants were inserted in the anterior region of the mandible and progressive loading was carried out with an increase in the distal cantilever. The length of the cantilever extension was adapted to growth of the residual alveolar bone at the mandible body. The increase in bone height was controlled in the area of implant placement as well as in the area distal to the implants (1 cm behind the last implant).This case series described 3 patients where 13 implants were placed. The patients were followed for 17, 19 and 20 years after implants insertion. The mean mandibular residual height of the alveolar bone was 7.8 ± 2.7 mm at the implant site. After one year of loading, the mean bone height at the insertion site of the implants was 10.0 ± 2.0 mm, representing a mean increase of 2.3 ± 1.5 mm. The mean mandibular body height at 1.0 cm distal to the last implant was 7.0 ± 3.9 mm in the third quadrant and 8.1 ± 4.4 mm in the fourth quadrant. The mean height at the last follow-up was 11.0 ± 3.2 mm (+/-3.2) in the third quadrant and 11.20 ± 4.4 mm in the fourth quadrant.Implant-supported prosthesis and progressive loading have resulted in vertical bone growth in a series of patients with extreme atrophy of the mandible. The long-term follow-up indicated that bone growth is confined to the dental implants but has been extended to distant regions resulting in the thickening of the mandibular body and the creation of the absent mandibular canal.